Survival of seropositive people to the human immune deficiency virus in a health area of Santiago de Cuba - Nancy Suárez Ramírez; Nancy Ivis Quiñones Suárez; Raxsy Soler Santana; Mayelin Marin Mendez (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The infection and the syndrome provoked by the human immune deficiency virus constitute the greatest problems lived worldwide.   Objective: To estimate the global survival from seropositive people to the human immune deficiency virus, diagnosed in the health area belonging to Josué País García Polyclinic in Santiago de Cuba.  Method: An observational, descriptive, of serial cases investigation, of 26 seropositive people to the human immune deficiency virus was carried out, they were diagnosed from January, 1998 to December, 2008, and residents in the mentioned health area in the moment of the diagnosis. The main analyzed variables were: sex, age, clinical stage when diagnosed and adherence to the antiretroviral therapy of high effectiveness.  Results: In the case material there was a prevalence of the male sex,  homosexuals, the diagnoses  carried out during the period of clinical latency and those no adherent to the treatment; also, it was evidenced that the mean time of survival surpassed half of the maximum time lived by the total of those investigated and that variables as  age,  clinical stage when diagnosed and adherence to the treatment didn't have an  important  level of statistical significance, taking into account the probability of surviving during the period of preset time.  The achieved global survival was of 92.3 %.   Conclusion: The obtained level of global survival surpassed the national and international standards.